2017
DOI: 10.1016/j.dyepig.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced debenzylation of 2,5-bis(dibenzylamino)-3,6-dichloro- p -benzoquinone

Abstract: In this detailed study of the photoreaction of 2,5-bis(dibenzylamino)-3,6dichloro-p-benzoquinone, two new products were separated along with the previously reported debenzylated analogues, and their molecular structure was determined. One compound was identified as 2-(benzylamino)-3,6-dichloro-5-(dibenzylamino)-p-benzoquinone, which was found to undergo further debenzylation to form the two known debenzylated analogues. The 2 other compound was identified as the hydroquinone form of the starting material. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Compound (1) ( Fig. 1) was synthesized following the procedure reported by Shin et al (2017), and its chemical structure was confirmed by conventional analytical techniques. The crystallization of (1) was carried out by the liquidliquid diffusion method in a thin glass tube, using a combi-nation of chloroform (good solvent) and methanol/ethanol (poor solvent).…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound (1) ( Fig. 1) was synthesized following the procedure reported by Shin et al (2017), and its chemical structure was confirmed by conventional analytical techniques. The crystallization of (1) was carried out by the liquidliquid diffusion method in a thin glass tube, using a combi-nation of chloroform (good solvent) and methanol/ethanol (poor solvent).…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…However, we could also prepare significant amounts of (1b) by crystallization of the quinone form of (1), which was also carried out by liquid-liquid diffusion, using a combination of chloroform and n-hexane as the good and poor solvents, respectively. The quinone form of (1) was transformed into the hydroquinone form by ambient light during crystallization (Shin et al, 2017). Thus, in contrast to the direct crystallization of (1), a considerable quantity of (1b) was obtained by this method.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…On the way to sustainable development, photocatalytic oxidation with molecular oxygen offers a promising strategy for green synthesis with reduced pollutants and energy consumption. The benzyl group has been widely utilized as a protecting group for wide applications in the multistep synthesis of drugs, , dyes, , fine chemicals, and energetic materials, resulting in widespread attention to debenzylation.…”
Section: Introductionmentioning
confidence: 99%